The agenda setting function of English newspapers during the 13th General Election - Chang, Peng Kee; Ali Salman,; Kho, Suet Ni; Mohd Rizal Mohd Yaakop,; Adisa, Rasaq M.; Ong, Choong Hoong (Penerbit Universiti Kebangsaan Malaysia, 2017)
It is opined that the mass media forces attention on certain issues by constantly projecting them and suggesting its audiences to think about them. This article attempts to focus on the Agenda Setting function of English news media in Malaysia during the 13th GE13 employing quantitative content analysis. Two English newspapers were analyzed, namely The Star and New Straits Times with 1362 news items identified. In order to gauge the public agenda, quantitative survey were done three times in the months of February, March and April 2013 respectively leading up to the election on 5th of May, 2013. The study found out that the agenda setting function of the English newspapers is important in transferring issue salience and issue attributes to their audiences. Individuals who highly rely on news from the media shall be likely influenced by the Agenda Setting effect of the media. There was no significant relationship between the English newspapers and the public agenda of the main ethnic groups in Malaysia. Hence, the public agenda of the Malays, Chinese and Indians have no significant relationship with the English Newspapers. Future studies could employ a qualitative approach in order to find answers to the reasons for lack of relationship between the English newspapers and ethnic public agenda.